Evaluation of Commercial Cultivars of Cut Gerbera (Gerbera jamesonii Bolus Ex Hooker F.) under Polyhouse in Shevaroy Condition of Eastern Ghats - Anand, M; Sankari, A; Arulmozhiyan, R (Journal of Horticultural Sciences, 2013)
An investigation was carried out to evaluate performance of 36 cultivars of cut gerbera (Gerbera jamesoniiBolus ex Hooker F.) in a polyhouse at Horticultural Research Station, Tamil Nadu Agricultural University, Yercaud, during 2008-2010. Significant differences were observed for all the characters studied. Maximum plant-spread (78.02cm) was observed in cv. Robusta. Higher number of leaves was recorded in cv. White Tibet (41.54). Maximum Leaf length and leaf width was recorded in cvs. Golden Gate and Yanara. Maximum number of suckers produced was recorded in cv. Junkfru (7.60). Maximum stalk length was observed in cv. White Tibet (62.62cm), while flower diameter, cut flower production and vase-life were higher in cv. Rosalin. Correlation and path coefficient analysis showed that plant height, number of leaves per plant and number of suckers per plant were the important components of cut-flower yield in gerbera. It may be concluded that cultivars Rosalin, White Tibet, Junkfru and Golden Gate were found to be the best for floral quality and yield, and are recommended for cut-flower production under Shevaroy condition of Eastern Ghats.